La flor, by Mariano Llinás: Cinema re-encounters literature - Almeida, Rogério de (Estudos Avançados, 2023)
The aim of this article is to study the relationship between cinema and literature in the film La flor (2018), by Argentine filmmaker Mariano Llinás. The method used is hermeneutics, by which we sought to investigate the interpretative perspectives emerging from the film and how they relate to the literary and cinematographic resources employed by the filmmaker, mainly through the exercise of style and the use of an extradiegetic narrator, responsible for the literary inflection of the film. Our findings show that, although the relationship between cinema and literature has been present in the history of cinema since the beginning, it gains a new contour in this film.